Tinjauan Teori Tindak Tutur terhadap Dampak Khotbah Radio Gereja Kristen Muria Indonesia Perjanjian-Nya, Kabanjahe di tengah Pandemi Covid-19 - Asyrelina March Br Barus; Irene Ludji (Sekolah Tinggi Teologi Jaffray Jakarta, 2022)
This article discusses the theory of speech acts on the impact of radio sermons by Gereja Kristen Muria Indonesia (GKMI) Perjanjian-Nya amid the COVID-19 pandemic. The method used in this research is qualitative descriptive. This article consists of three parts. In the first part, the author discusses the service carried out by GKMI Perjanjian-Nya through radio sermons during the pandemic. In the second part, the writer discusses the speech act theory pioneered by John Langshaw Austin and developed by Anna Cho. The speech act theory used in the analysis of this article is based on the definitions of locutions, illocutions, and perlocutions described by Cho. In the third part, the author describes the data from the research and analyses it using the speech act theory. This article concludes that the radio sermon service carried out by GKMI Perjanjian-Nya fulfills the requirements for locutionary, illocutionary, and perlocutionary acts, which are the three main parts of speech act theory. Hearing sermons on the radio helps the community's spiritual growth, as seen through the ability to take ethical responsibility in the form of practices that are in line with God's word preached through the radio.